Penerapan Digital Financial Reporting untuk Meningkatkan Transparansi dan Pengambilan Keputusan Keuangan pada UMKM Sozo Salon - Yanti, Evi; Haryanto, Hery (Pakis Journal Institute, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a vital role in the national economy; however, many MSMEs still lack structured financial recording systems. Sozo Salon MSME in Batam City is a service-based business that previously did not prepare systematic income statements, making it difficult for business owners to assess financial performance and make informed decisions. This community service activity aims to improve financial transparency and decision-making quality through the implementation of digital financial reporting using the Zenwel Biz application. The methods employed include observation, interviews, digital financial recording system design, implementation assistance, and monitoring and evaluation. The results indicate that the partner is able to record revenue and expense transactions digitally and generate automatic periodic income statements. The outputs include the implementation of a digital financial recording system, automated income statements, and a system user guide. Overall, this activity enhances financial management understanding, business transparency, and supports more structured and sustainable financial decision-making for MSMEs.